Protective Mechanism of Luteinizing Hormone and Follicle-Stimulating Hormone Against Nicotine-Induced Damage of Mouse Early Folliculogenesis - Liu, Wen-Xiang; Zhang, Yan-Jie; Wang, Yu-Feng; Klinger, Francesca Gioia; Tan, Shao-Jing; Farini, Donatella; De Felici, Massimo; Shen, Wei; Cheng, Shun-Feng (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have shown that nicotine could impair the germ cell cyst breakdown and the primordial follicle assembly by autophagy. In this paper, we discovered that luteinizing hormone (LH) and follicle-stimulating hormone (FSH) could counteract the damage caused by nicotine of mouse germ cell cyst breakdown. The neonatal mice were separately intraperitoneally injected with nicotine, nicotine plus LH, nicotine plus FSH, and saline (control) for 4 days. Compared with the nicotine group, the quality of oocytes and the number of follicles were remarkably increased in nicotine plus LH group or nicotine plus FSH group. LH and FSH could alleviates nicotine-induced oocytes autophagy by different pathways. LH reduced the nicotine-induced autophagy by restoring the phosphorylation level of AMPKα1, while FSH by down-regulating the phosphorylation level of FOXO1. In addition, in subsequent study of six-week mice in different treated group, we found that LH and FSH supplementation significantly improved normal maturation rates, fertilization rates and embryo's developmental potential of oocytes in oocytes exposed to nicotine. Taken together, these results suggested that LH and FSH could counteract the damage caused by nicotine and finally ensure the normal of germ cell cyst breakdown and early embryo development.